Evaluation of antimicrobial activity of Lactobacillus acidophilus and Lactobacillus rhamnosus against clinically isolated Klebsiella pneumoniae: an in vitro study - Anil, Anju; Raj, Ananthu; M. M., Azhar; Kuriakose, Nithyamol; Murali, Radhika; Kumar K. S., Harish (International Journal of Research in Medical Sciences, 2024)
Background: Klebsiella pneumoniae are Gram-negative opportunistic pathogen, belonging to the family Enterobacteriaceae that can cause severe nosocomial infections particularly in immuno-compromised individuals. They exhibit co-resistance to multiple antibiotics which emphasize the need for non-antibiotic therapies. The goal of the presented study was to investigate the antimicrobial ability of probiotic Lactobacilli on clinical isolates of K. pneumoniae. Methods: In this cross-sectional study, antimicrobial activities of probiotic L. acidophilus and L. rhamnosus on K. pneumoniae were evaluated by Agar overlay interference technique. Clear zone around Lactobacilli were taken as positive inhibition. Antibiotic susceptibility profiles of K. pneumoniae were determined by Kirby-Bauer disk diffusion method, analyzed using interpretive standards of CLSI M100-S33 and categorized into MDR, XDR and Non MDR groups. Statistical analysis was done using descriptive statistics such as mean and standard error and inferential statistics such as ANOVA single factor. Results: K. pneumoniae exhibited positive inhibition with both the probiotic strain. On comparing the zone of inhibition of L. acidophilus and L. rhamnosus (both treated-pH adjusted and untreated), L. acidophilus had greater zone of inhibition against K. pneumoniae but concluded that statistically the values are insignificant (p>0.05). Based on antibiotic susceptibility pattern of K. pneumoniae, 63% of isolates were XDR, 3% were MDR and 34% were Non MDR Conclusions: It can be concluded that L. acidophilus and L. rhamnosus had significant inhibitory effect against K. pneumoniae in vitro and should be further studied for their human health benefit.